Hiding out at the Pancake Palace - Marino, Nan (Roaring Brook Press, 2013)
"When musical prodigy, Elvis Ruby, completely freezes up on television, he is forced to hide out in the Pinelands of New Jersey and try to find his way back to the music once again with the help of a new friend"--